2003
DOI: 10.1037/0736-9735.20.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Attachment to the therapist.

Abstract: This study examines the ways in which therapists function as attachment figures for patients. Patients in long-term psychoanalytic therapy answered questionnaires about their feelings about their therapists and their closest personal relationships. Components of attachment prominent in the therapeutic relationships were looking up to the therapist and feeling the therapist was responsive to emotional needs. Stronger attachment to therapists was associated with greater frequency and duration of therapy, a stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 33 publications
4
74
1
6
Order By: Relevance
“…Responses were rated on a 7-point Likert-type scale ranging from 1 (strongly disagree) to 7 (strongly agree). The construct validity and internal reliability was supported in the validation of the CAQ (Parish, 2000) and has since been cross-validated in a study conducted by Parish and Eagle (2003). Cronbach's alpha for the three subscales within the current sample demonstrated satisfactory scores: proximity maintenance, α = 0.85; safe haven, α = 0.72; and secure base, α = 0.83.…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…Responses were rated on a 7-point Likert-type scale ranging from 1 (strongly disagree) to 7 (strongly agree). The construct validity and internal reliability was supported in the validation of the CAQ (Parish, 2000) and has since been cross-validated in a study conducted by Parish and Eagle (2003). Cronbach's alpha for the three subscales within the current sample demonstrated satisfactory scores: proximity maintenance, α = 0.85; safe haven, α = 0.72; and secure base, α = 0.83.…”
Section: Methodsmentioning
confidence: 90%
“…Attachment researchers (Collins & Read, 1990;Davidovitz, Mikulincer, Shaver, Izsak, & Popper, 2007;Hazan & Shaver, 1987;Parish & Eagle, 2003) have extended infant-caregiver attachment to such adult relationships. Although recent empirical research on adult attachment has focused on areas such as leadership (Davidovitz et al, 2007), therapy (Parish & Eagle, 2003), and friendship (Granot & Mayseless, 2001;Wilkinson, 2008), most of the research conducted to date has focused on adult romantic relationships (see , for a full review).…”
Section: Attachment Theory In Adulthoodmentioning
confidence: 99%
See 1 more Smart Citation
“…In many ways, the therapist does act as an attachment figure or at least a secondary attachment figure for the client (Farber et al 1995;Hill 2005;D'Elia 2001;Parish and Eagle 2001;Sterlin 2006). Treatment activates the attachment system in that it replicates many of the characteristics of the early parent-child bond.…”
Section: Research On Attachmentmentioning
confidence: 97%
“…Indeed, Crowell et al (1996) found that when applying an AAIlike classifi cation strategy to an interview about employment experiences, there was no overlap of classifi cation in persons assessed with both interviews. It might be that psychotherapy is an attachment-relevant situation by design, in that the process of seeking help might activate the attachment behavioural system and thus, perhaps, the related discourse patterns (Dozier & Bates, 2004;Parish & Eagle, 2003). On the other hand, in psychotherapy, attachment relationships are not necessarily discussed, and the verbal activity of the therapist may be very different from that of the AAI interviewer, who consistently pushes for immersion in attachment themes.…”
Section: Introductionmentioning
confidence: 97%